OBESOGENIC ENVIRONMENT IN INDONESIA: A LITERATURE REVIEW OF ENVIRONMENTAL DETERMINANTS OF OBESITY - Latifah , Suci; Khusun, Helda; Kekalih, Aria; Basrowi, Ray Wagiu (Journal of Indonesian Specialized Nutrition, 2025)
Background: Obesity is a complex public health issue influenced by multiple determinants, including environmental factors that promote excessive calorie intake and physical inactivity, known as obesogenic environments. Objective: This literature review is to broaden understanding the environmental determinants of obesity in Indonesia. Method: A narrative literature review was conducted focusing on studies published between 1999 and 2024. Sources were retrieved from databases including PubMed, WHO Global Health Observatory, and national health surveys such as Riskesdas. The ecological framework by Swinburn et al. (1999) was used to analyse environmental influences on obesity. Results: Findings indicate that built and food environments play significant roles in shaping obesity patterns in many places. Studies show increasing obesity prevalence in both urban and rural Indonesia, with environment-related factors such as food availability, urbanization, and reduced physical activity opportunities contributing to this trend. Conclusion: Food environment, land use and physical infrastructure were identified as potential proxies for obesogenic environments in Indonesia. Further studies are needed to evaluate and validate these proxies to support the development of environments conducive to healthy lifestyles and to reduce obesity prevalence.